Surface plasmon resonance for bio/chemical sensing - Ng, Weijian. (2012)
In this current modern era, the demand for fast, accurate, efficient and real time analysis method is always increasing, and it has driven tremendous progress towards smaller, faster, and more efficient detection devices in silicon industry over the past five decades. Nanophotonics, which is defined as the science and engineering of light-matter interactions that take place on wavelength and subwavelength scales (eg. in nanometer scale), is believed to be next generation chip scale technology. Comsol Multiphysics, a frontier research computational tool will be used for design of structures, characterization of device and analysis purpose.